2018
DOI: 10.1245/s10434-018-6360-6
|View full text |Cite
|
Sign up to set email alerts
|

Solitary Pulmonary Lesion in Patients with History of Malignancy: Primary Lung Cancer or Metastatic Cancer?

Abstract: Incidence of malignant SPLs was fairly high in patients with history of malignancy. A nomogram including site and lymph node status of primary tumor, and spiculation and location of SPL might be a good tool for differentiating PLC from intrapulmonary metastasis preoperatively and guiding treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
0
6
1
Order By: Relevance
“…28 Nonetheless, there are several articles that state the opposite. 24,29 We did not find any family history of cancer or adjuvant therapy as a factor of NLC in our study.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…28 Nonetheless, there are several articles that state the opposite. 24,29 We did not find any family history of cancer or adjuvant therapy as a factor of NLC in our study.…”
Section: Discussioncontrasting
confidence: 65%
“…Size and SUV max of the PLs were investigated as predictive factors of NLC; some sources stated (<3 cm) smaller lesions 29 while several others expressed that larger lesions (>3 cm) were more frequent in their studied NLC groups. 17 Nakadate et al revealed that NLC patients had significantly larger PLs, which also have significantly higher SUV max uptakes than PM patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Solitary pulmonary lesions (SPLs) can be categorized into various types [1][2][3], such as tumors and inflammatory or tuberculous granulomas. Early identification and differentiation of benign and malignant lesions, especially in lung cancer are of great significance to guiding clinical treatment protocols and improving prognoses [4].…”
Section: Introductionmentioning
confidence: 99%
“…Another issue is the lack of histological proof in one patient. However, radiographic evidence such as peripheral sites, lack of spiculation and the absence of nodal lung or mediastinal extension can be helpful tools to determine whether an isolated nodule is a primary or a secondary disease [30].…”
Section: Discussionmentioning
confidence: 99%